Nutrient Utilization, Milk Yield and Economics of Production in Crossbred Cows Fed Berseem Hay Meal Supplemented Diet - das, madan mohan; Sultan Singh; P. Sharma; Khem Chand (Indian Journal of Animal Nutrition, 2023)
The replacement effect of mustard cake protein with berseem hay meal protein in concentrate mixture was studied for nutrient utilization, milk yield and economics of production in crossbred cows. In the control group(G1), the animals were fed control concentrate mixture with wheat straw ad libitum whereas in the treated group (G2), 60% N of mustard cake was replaced with berseem hay meal in the concentrate mixtures along with wheat straw ad libitum for a period of two and half months. Both the groups were provided iso-energetic and iso nitrogeneous diet. The intake of dry matter either as percentage of body weight or per kg metabolic body size was comparable between the groups. Similarly, the digestibility of nutrients viz.DM, OM, NDF and ADF were similar in both the groups. Milk yield (7.02 Vs 7.21 kg/d) and composition of milk of animals fed with or without supplementation of BHM was also non- significantly different indicating that legumes did not change the composition of milk. Feed conversion efficiency for milk production and N utilization efficiency was also similar between the groups. Average daily feeding cost and cost of milk production(Rs/kg 4%FCM) reduced (P<0.05) by 13.89 and 17.53%, respectively in cows fed experimental diet, hence net daily income was increased (P<0.05) by Rs. 26.71 per cow. It may be concluded that mustard cake can safely be replaced by berseem hay meal(BHM) in iso-caloric and iso-nitrogeneous diet in formulating least cost ration for economic milk production in small holders’ dairy production without compromising the feed intake, nutrient utilization and milk yield of crossbred cows.